2016
DOI: 10.1016/j.biomaterials.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Matrix rigidity differentially regulates invadopodia activity through ROCK1 and ROCK2

Abstract: ROCK activity increases due to ECM rigidity in the tumor microenvironment and promotes a malignant phenotype via actomyosin contractility. Invasive migration is facilitated by actin-rich adhesive protrusions known as invadopodia that degrade the ECM. Invadopodia activity is dependent on matrix rigidity and contractile forces suggesting that mechanical factors may regulate these subcellular structures through ROCK-dependent actomyosin contractility. However, emerging evidence indicates that the ROCK1 and ROCK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 124 publications
(191 reference statements)
6
99
0
Order By: Relevance
“…Previous studies have shown that invadopodia become more enzymatically active in response to changes in ECM rigidity (Jerrell and Parekh, 2016;Parekh and Weaver, 2016) but the maturation of invadopodia in response to contractile tugging forces present within the ECM has not been examined. In our assay, invasion occurred at a basal level without mechanical stimulation, but only in cells known to be invasive, suggesting that existing invasive machinery, such as invadopodia, were functioning without mechanical stimulation.…”
Section: In Vitro Mechanical Stimulation Results In the Lengthening Omentioning
confidence: 99%
“…Previous studies have shown that invadopodia become more enzymatically active in response to changes in ECM rigidity (Jerrell and Parekh, 2016;Parekh and Weaver, 2016) but the maturation of invadopodia in response to contractile tugging forces present within the ECM has not been examined. In our assay, invasion occurred at a basal level without mechanical stimulation, but only in cells known to be invasive, suggesting that existing invasive machinery, such as invadopodia, were functioning without mechanical stimulation.…”
Section: In Vitro Mechanical Stimulation Results In the Lengthening Omentioning
confidence: 99%
“…We have previously verified that cells are exposed to the same relative amounts of fibronectin on the surfaces of these PAAs based on the use of increasing concentrations of fibronectin (200, 215, and 230 μg/ml, respectively) . For traction force assays, PAAs also contained 200 nm fluorescent beads which do not change their mechanical properties . Cells were incubated on PAAs for 1 or 18 hours prior to immunostaining and/or traction force microscopy.…”
Section: Methodsmentioning
confidence: 96%
“…Soft, hard, and rigid fibronectin‐conjugated PAAs with elastic moduli of 1,023, 7,307, and 22,692 Pa, respectively, were cast on activated coverslips of 35 mm MatTek dishes (MatTek, Ashland, MA) as previously described . These PAAs were composed of 8%/0.05%, 8%/0.35%, and 12%/0.6% acrylamide/BIS ratios, respectively, as well as 0.1% N ‐hydroxysuccinimide ester which polymerizes into the polyacrylamide network and binds protein throughout the gels.…”
Section: Methodsmentioning
confidence: 99%
“…This enhancement of invadopodium maturation is dependent on the acto-myosin contractile apparatus, suggesting that invading tumor cells respond to more than just chemical cues encountered in the ECM, and that the actin cytoskeleton dynamically adapts to changes in matrix rigidity that require proteolysis for tumor cell migration [59, 61]. The effect of ECM rigidity on invadopodium maturation is mediated by the different effects of Rho-associated kinase ROCK1/2 [62]. ROCK1/2 accomplishes this by regulating both the acto-myosin contractile apparatus via non-muscle myosin II activation, and direct regulation of LIM kinase’s phosphorylation of cofilin to spatially couple Rho-G protein activity to the activation of cofilin-induced actin polymerization in the invadopodium core [10, 15, 63], leading to invadopodium maturation and modulation of invadopodium shape [6264] and turnover [19, 48].…”
Section: Diverse Stimuli Initiate Invadopodium Formation In Diverse Mmentioning
confidence: 99%